Accounting for stock-based compensation: an extended clean surplus relation - Dieter E. Hess; Erik Lüders (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2001)
Residual income valuation is based on the assumption that the clean surplus relation holds. As pointed out by Ohlson (2000), among others, the standard clean surplus relation is frequently violated. Moreover, standard residual income valuation models rest on the implicit assumption that future stated earnings belong to current shareholders only. This is clearly invalid for companies granting employee options. In order to overcome these deficiencies, this paper establishes an extension of the clean surplus relation and derives simple analytical solutions for the value of outstanding stocks in terms of already known accounting information.
Keywords: G12; M41; 330; Residual income valuation; clean surplus accounting; US-GAAP; employee stock option programs; Gewinnermittlung; Börsenkurs; Leistungsorientierte Vergütung; Aktienoption; Bilanz; Grundsätze ordnungsmäßiger Buchführung; Informationswert; Theorie